EFEKTIFITAS UNIT PELAKSANA TEKNIS (UPT) PEMELIHARAAN JALAN DAN DRAINASE WILAYAH BARAT DINAS PEKERJAAN UMUM DAN PENATAAN RUANG (PUPR) KOTA TANGERANG DALAM PEMELIHARAAN JALAN DI KECAMATAN PERIUK KOTA TANGERANG - Subagia, Dodi; Miftahul Huda , Muhammad (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study aims to examine the effectiveness of the Technical Implementation Unit (UPT) for Road and Environmental Maintenance of the Western Region under the Department of Public Works and Spatial Planning (PUPR) of Tangerang City in maintaining roads in the Periuk District. The background of this research stems from the importance of road infrastructure quality as a key factor in supporting public mobility and regional economic growth. This study employs a qualitative approach, using data collection techniques such as observation, interviews with the UPT head, sub-division head, field officers, and road users from the community, as well as documentation. Data analysis was conducted based on five effectiveness indicators proposed by Sutrisno: program understanding, target accuracy, timeliness, goal achievement, and tangible changes. The results indicate that the UPT has demonstrated a strong understanding of the program, and that road maintenance activities are generally well-targeted and implemented within the planned time frame, despite some technical challenges. Most of the program objectives have been achieved, and tangible improvements in road conditions are evident and appreciated by the community. The study concludes that the road maintenance program carried out by the UPT can be categorized as moderately effective. However, there is still a need for improvement in terms of equitable implementation, budget management, and stronger coordination and communication among stakeholders to ensure that the benefits of the program are fully realized by the broader community.